Cycle Stability of the Effective Thermal Conductivity of Nickel‐Activated Magnesium Hydride Powder under Operating Conditions. Issue 10 (13th August 2020) - Albert, Rene; Wagner, Christian; Urbanczyk, Robert; Felderhoff, Michael
Abstract : Herein, the transient plane source (TPS) method is used to investigate the effective thermal conductivity (ETC) of nickel‐activated magnesium hydride powder (MgH2 with 4 mass% Ni) under operating conditions at temperatures up to 400 °C and a hydrogen pressure up to 25 bar. MgH2 together with Ni can be used as heat storage material and is synthesized by mixing of the respective metal powders with subsequent temperature‐controlled hydrogenation and dehydrogenation cycles under hydrogen gas pressure. Running a hydrogenation and dehydrogenation cycle test of nickel‐activated magnesium hydride for more than 450 cycles shows a tremendous enhancement of the ETC. It can be shown that the ETC value of the MgH2 powder under hydrogen atmosphere depends on the sample temperature, the applied gas pressure, and the cycle number. The maximum ETC of dehydrogenated nickel‐activated magnesium hydrides is above 8 W m −1  K −1 at 15 bar, 400 °C, and after 201 cycles. An investigation by electron microscopy shows a percolated network of dehydrogenated magnesium hydride particles which is formed by sintering during the dehydrogenation steps and which is responsible for the enhanced thermal conductivity. Abstract : The transient plane source (TPS) method is used to investigate the effective thermal conductivity (ETC) of nickel‐activated magnesium hydride powder (4 mass% Ni) under operating conditions up to 400 °C and a hydrogen pressure up to 25 bar. The maximum ETC of dehydrogenated material is above 8 W m −1  K −1 at 15 bar, 400 °C, and after 201 cycles.